Indonesia’s monetary integration with OIC member countries: new evidence - Agustiar, Memet (Penerbit Universiti Kebangsaan Malaysia, 2019)
The purpose of this paper is to assess the co-movement of currency symmetry between Indonesia and the Organization of Islamic Conference (OIC) members. The contemporary progress of economic relations between Indonesia and the OIC members might push them towards monetary integration. By employing the Optimum Currency Area (OCA)-index, this study finds that Indonesia has a strong monetary integration with the OIC members. Indonesia is found to be within the top 10 prime converged countries in the OIC. This finding is clearly contradictory to previous studies that mostly identified little integration between Indonesia and other countries. The panel fixed-effect least squares regression model estimates that the similarity in inflation is the only significant criterion in explaining the closer integration of Indonesia with the OIC. This study provides a new policy implication for Indonesia to integrate more widely within the canopy of the OIC: as long as price stability can be maintained, the potential for integration will be greater.